2011
DOI: 10.7201/earn.2007.13.04
|View full text |Cite
|
Sign up to set email alerts
|

La importancia del atributo origen en la elección de productos agroalimentarios. El caso del espárrago de Navarra

Abstract: RESUMEN:En este trabajo se analiza la importancia de los atributos extrínsecos en la elección del consumidor para la categoría del espárrago blanco, prestando especial atención a la influencia del origen y a la de la denominación de origen espárrago de Navarra. Para ello, se diseña un experimento que incluye 18 pantallas de elección con alternativas formadas por combinaciones de dichos atributos. Los resultados se analizan mediante un modelo logit multinomial que permite valorar la importancia de los atributos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…It is important for product designers to know which quality indicators are relevant to consumers, since this will enable them to design products that match consumers' needs and preferences, as recent research has shown (Bello & Calvo, 2000;Cortiñas, Chocarro, Elorz, & Villanueva, 2007;Lockshin, Jarvis, d'Hauteville, & Perrouty, 2006;Verbeke & Ward, 2006;Westerlund, 2007). From the marketing point of view, moreover, the importance of extrinsic quality cues lies in the fact that they can be manipulated without the need for any physical alterations to the product.…”
Section: Introductionmentioning
confidence: 94%
“…It is important for product designers to know which quality indicators are relevant to consumers, since this will enable them to design products that match consumers' needs and preferences, as recent research has shown (Bello & Calvo, 2000;Cortiñas, Chocarro, Elorz, & Villanueva, 2007;Lockshin, Jarvis, d'Hauteville, & Perrouty, 2006;Verbeke & Ward, 2006;Westerlund, 2007). From the marketing point of view, moreover, the importance of extrinsic quality cues lies in the fact that they can be manipulated without the need for any physical alterations to the product.…”
Section: Introductionmentioning
confidence: 94%
“…Cuando un cliente es considerado extremadamente fiel no considera a otras empresas a las que comprar, es decir, las alternativas no son 219 Tal y como apuntan investigadores como Carmona et al (2008), Cortiñas et al (2000), entre otros. Carmona A., Lela A.…”
Section: 41-lealtadunclassified